PENGARUH KEUNIKAN KAPABILITAS DAN TURBULENSI LINGKUNGAN TERHADAP STRATEGI KORPORASI DAN DAMPAKNYA PADA KINERJA UNIVERSITAS (Studi Tentang Universitas di Kopertis Wilayah III Jakarta) - Virgo Simamora (JOURNAL OF BUSINESS STUDIES, 2016)
Abstract As the title implies, this study aims to examining the effect of the distinctive capabilities and environmental turbulences on the university performances through corporate strategy. Distinctive capability is a unique capability by which an organization distinguishes itself from its competitors. This study defines that the uniqueness of capabilities is created through the long term routine activities in such a way that an organization is capable of developing a skill that is hard to duplicate. Environmental turbulence is a situation characterized by dynamic changes in which the organization facing a complex and uncertain environment that may lead to potential turbulences. The higher educational industry in Indonesia faces turbulences as the effects of globalization, information technology changes and frequent regulatory changes. It is found that most universities in Jakarta have no unique capability yet. This research found that distinctive capabilities and environmental turbulences are the exogenous variables that directly effect corporate strategy. The research also reveals that the corporate strategy effect the performance of university. Furthermore, this research also found that the university performances are indirectly influenced by the distinctive capabilities through corporate strategy. Similarly, the university performances are indirectly influenced by environmental turbulences through corporate strategy. The research shows that the effect of the distinctive capabilities are higher than the effect of the environmental turbulences. To summarize, the distinctive capabilities and environmental turbulences have influenced the performances of universities through corporate strategy in Jakarta. To improve their performances, the universities have to enhance their distinctive capabilities and increase their ability in responding to the environmental changes. Keywords : distinctive capabilities, environmental turbulences, corporate strategy, organizational    performances Abstrak   Keunikan kapabilitas adalah kapabilitas istimewa yang menunjukkan bahwa organisasi dapat melakukan sesuatu lebih baik dari kompetitornya. Di dalam penelitian ini, keunikan kapabilitas terbentuk dari aktivitas rutin universitas yang diselenggarakan dalam jangka waktu yang panjang sehingga menjadi keahlian yang sulit ditiru, Turbulensi lingkungan adalah situasi yang ditandai dengan terjadinya lingkungan yang dinamis, kompleks dan tidak pasti yang berpotensi menimbulkan turbulensi lingkungan. Di industri pendidikan tinggi, turbulensi terjadi akibat globalisasi, perubahan tekologi informasi dan perubahan regulasi dalam intensitas yang tinggi dan waktu yang cepat. Menurut hasil penelitian terdapat pengaruh keunkan kapabilitas dan turbulensi lingkungan terhadap strategi korporasi. Dalam hal ini, keunikan kapabilitas memberikan kontribusi yang lebih besar dalam mempengaruhi strategi korporasi. Penelitian ini juga menemukan bahwa terdapat pengaruh strategi korporasi terhadap kinerja universtias, Hasil penelitian juga menunjukkan bahwa ada pengaruh tidak langsung keunikan kapabilitas terhadap kinerja universitas melalui strategi korporasi dan ada pengaruh tidak langsung turbulensi lingkungan terhadap kinerja universitas terhaap strategi korporasi. Hasil penelitian telah memberikan pemikiran baru bahwa kinerja universitas di lingkungan Kopertis Wilayah III Jakarta dapat diperbaiki dengan meningkatkan keunikan kapabilitas universitas, meningkatkan kemampuan universitas merespon lingkungan sebagai peluang yang mempengaruhi strategi korporasi universitas. Kata kunci : keunikan kapabilitas, turbulensi lingkungan, strategi korporasi, kinerja